Home-Use Evaluation of a Wearable Collision Warning Device for Individuals With Severe Vision Impairments: A Randomized Clinical Trial - Pundlik, Shrinivas (JAMA Ophthalmol, 2021)
IMPORTANCE: There is scant rigorous evidence about the real-world mobility benefit of electronic mobility aids. OBJECTIVE: To evaluate the effect of a collision warning device on the number of contacts experienced by blind and visually impaired people in their daily mobility. DESIGN, SETTING, AND PARTICIPANTS: In this double-masked randomized clinical trial, participants used a collision warning device during their daily mobility over a period of 4 weeks. A volunteer sample of 31 independently mobile individuals with severe visual impairments, including total blindness and peripheral visual field restrictions, who used a long cane or guide dog as their habitual mobility aid completed the study. The study was conducted from January 2018 to December 2019. INTERVENTIONS: The device automatically detected collision hazards using a chest-mounted video camera. It randomly switched between 2 modes: active mode (intervention condition), where it provided alerts for detected collision threats via 2 vibrotactile wristbands, and silent mode (control condition), where the device still detected collisions but did not provide any warnings to the user. Scene videos along with the collision warning information were recorded by the device. Potential collisions detected by the device were reviewed and scored, including contacts with the hazards, by 2 independent reviewers. Participants and reviewers were masked to the device operation mode. MAIN OUTCOMES AND MEASURES: Rate of contacts per 100 hazards per hour, compared between the 2 device modes within each participant. Modified intention-to-treat analysis was used. RESULTS: Of the 31 included participants, 18 (58%) were male, and the median (range) age was 61 (25-73) years. A total of 19 participants (61%) had a visual acuity (VA) of light perception or worse, and 28 (90%) reported a long cane as their habitual mobility aid. The median (interquartile range) number of contacts was lower in the active mode compared with silent mode (9.3 [6.6-14.9] vs 13.8 [6.9-24.3]; difference, 4.5; 95% CI, 1.5-10.7; P < .001). Controlling for demographic characteristics, presence of VA better than light perception, and fall history, the rate of contacts significantly reduced in the active mode compared with the silent mode (β = 0.63; 95% CI, 0.54-0.73; P < .001). CONCLUSIONS AND RELEVANCE: In this study involving 31 visually impaired participants, the collision warnings were associated with a reduced rate of contacts with obstacles in daily mobility, indicating the potential of the device to augment habitual mobility aids. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03057496